Mathematical Modeling of Silicon Doping by Neutron Transmutation Doping Method for High Efficient Solar Cells. (15th May 2017) - Dshkhunyan, Valery L.; Dyakov, Alexander A.; Karabanov, Sergey M.; Kozlov, Andrey V.; Markov, Dmitry V.; Hoshino, Masahiro
ABSTRACT: It is known that n-Si solar cells have higher efficiency than p-Si solar cells. One of the problems connected with n-Si application for solar cell production is the difficulty of using Czochralski method for growing n-Si ingots, uniform in structure. The present paper examines the possibility of production of n-Si ingots, uniform in resistance, by neutron transmutation doping (NTD) for photovoltaics using the mathematical modeling method. The provided calculation data are obtained by MCU-RFFI/A accounting code with DLC/MCUDAT-1.0 constant library developed by «Kurchatov Institute» Russian Research Center. The MCU accounting code is used for solution of the neutron-transport equation by Monte-Carlo procedure on the basis of estimated nuclear data for arbitrary three-dimensional geometry systems. The present paper provides the estimation of uniformity of neutron-flux density along the ingot length and radius; dependence of silicon resistance on duration of irradiation. These studies established the neutron flux density distribution along the ingot length and radius; regularities of silicon resistance changes on duration and intensity of irradiation.